Tumor aneuploidy in young patients with colorectal cancer - Kearney, T J; Price, E A; Lee, S; Silberman, A W (Cancer, 1993)
Colorectal cancer in young patients (40 years of age or younger) often is considered to have a worse prognosis than in older patients. The authors studied tumor DNA status and stage of disease to determine whether tumors in younger patients behaved differently from tumors in older patients. This retrospective study identified 33 young patients with colorectal cancer treated surgically between 1979 and 1989. The DNA content of the tumors was analyzed by DNA flow cytometry. Results were compared with 75 cases of colon cancer in patients older than 40 years of age. Six of the 33 young patients had inadequate tissue for study. Four patients with ulcerative colitis were excluded. Tumor aneuploidy was present in 14 of 23 young patients (61%; mean age, 35 years) and 46 of 75 older patients (61%; mean age, 71 years). When Dukes staging was performed for the young patients, one had Stage A (4%), nine had Stage B (39%), eight had Stage C (35%), and five had Stage D (22%) disease. The control group had similar staging. The distribution of aneuploid tumors within each Dukes stage was also similar. Twenty-one young patients were available for follow-up. Four (31%) of 13 patients with aneuploid tumors died, whereas none of 8 patients with diploid tumors died. This trend was not statistically significant (P < 0.10). The frequency of tumor aneuploidy, stage of disease at presentation, and distribution of tumor aneuploidy within each stage was similar when young and old patients with colorectal cancer were compared. There is a trend toward tumor aneuploidy being associated with a poorer prognosis in young patients.